2015
DOI: 10.1364/oe.23.019242
|View full text |Cite
|
Sign up to set email alerts
|

Fourier-based interpolation bias prediction in digital image correlation

Abstract: Based on the Fourier method, this paper deduces analytic formulae for interpolation bias in digital image correlation, explains the well-known sinusoidal-shaped curves of interpolation bias, and introduces the concept of interpolation bias kernel, which characterizes the frequency response of the interpolation bias and thus provides a measure of the subset matching quality of the interpolation algorithm. The interpolation bias kernel attributes the interpolation bias to aliasing effect of interpolation and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 40 publications
0
35
0
4
Order By: Relevance
“…As far as images of grids of nominal pitch p are concerned, it is possible to further simplify Equation 52. The spectrum of grid images has been thoroughly studied in [45] by using the stationary phase method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as images of grids of nominal pitch p are concerned, it is possible to further simplify Equation 52. The spectrum of grid images has been thoroughly studied in [45] by using the stationary phase method.…”
Section: Resultsmentioning
confidence: 99%
“…The nature of the function used to perform this interpolation strongly influences the amplitude of this phenomenon. This amplitude is therefore difficult to predict and a wide literature is available on this subject, see [50,51,52] for instance. Note that other strategies than back-deforming the current image in the reference coordinate system can be used while performing DIC (see the comprehensive review in [53]), but the presence of a systematic error is observed in all cases.…”
Section: Digital Image Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct images can be readily obtained using 3D-DIC. The accuracy of this method was determined through a coupling factor that takes into account the image noise, interpolation bias, and the calculation algorithm parameters [32]. Establishing the theoretical measurement resolution for high-gradient deformation conditions (e.g., within Lüders or the PLC band) is difficult.…”
Section: Methodsmentioning
confidence: 99%
“…While using digital screens as reference for DIC measurements has been done before, it has not been used for top-down quantification of the measurement error. 8 The method is fully described in European Patent Application EP 30 26 632 AP. 9 The core idea of the method is to make DIC measurements more acceptable in an industrial setting.…”
Section: Introductionmentioning
confidence: 99%